Application of Distributed Acoustic Sensing for Active Near-Surface Seismic Monitoring - Eslam Roshdy; Mariusz Majdański; Szymon Długosz; Artur Marciniak; Paweł Popielski (Sensors)
High-resolution imaging of the near-surface structures of critical objects is necessary in various applications including geohazard studies, the structural health of artificial structures, and generally in environmental seismology. This study explores the use of fiber optic sensor technology in active seismic surveys to monitor the embankment structure of the Rybnik Reservoir in Poland. We discuss the technical aspects, including sensor types and energy sources, and provide a comparison of the data collected with a standard geophone-based survey conducted simultaneously. A thorough data processing methodology is presented to directly compare both datasets. The results show a comparable data quality, with DAS offering significant advantages in terms of both the spatial and temporal resolution, facilitating more accurate interpretations. DAS demonstrates its ability to operate effectively in complex geological environments, such as areas with high seismic noise, rough terrain, and variable surface conditions, making it highly adaptable for monitoring critical infrastructure. Additionally, DAS provides long-term monitoring capabilities, essential for ongoing structural health assessments and geohazard detection. For example, the multichannel analysis of surface waves (MASW) using DAS data clearly identifies S-wave velocities down to 13 m with an RMS error of 3.26%, compared to an RMS error of 6.2% for geophone data. Moreover, the DAS-based data were easier to process and interpret. The integration of DAS with traditional seismic data can provide a more comprehensive understanding of subsurface properties, facilitating more accurate and reliable geophysical assessments over time. This innovative approach is particularly valuable in challenging environments, underscoring its importance in monitoring critical infrastructure.